Hypsochlorins - Larsen, Simon; Conradie, Jeanet; Desbois, Nicolas; Gros, Claude P.; Ghosh, Abhik (Comptes Rendus. Chimie)
Both the Soret and Q bands of chlorin e6 complexes blueshift on going from Zn to Pd to Pt as the coordinated metal, establishing the latter two complexes as hypsochlorins. DFT/TDDFT calculations indicate that the blueshifts appear to be related to the presence of the electronegative metal ion, which lowers the orbital energies of the HOMO and HOMO-1, while leaving the LUMOs relatively unaffected.